The Workplace spiritual influence in the attitudes of worker At a number of hospitals, health department BAGHDAD/ Rusafa - الشيخلي, عبد الرزاق ابراهيم; رحيمة, سلمى حتيتة (Journal of Economics and Administrative Sciences, 2017)
Spiritual is one of modern subjects gained importance of their role in the meaning imparted to work and to promote a sense of belonging to the group and the community, including support personnel positive attitudes towards their work. The research aims to highlight the impact of the relationship between workplace spiritual and variable working attitudes to sample variant of the hospitals, health department BAGHDAD / Rusafa, and in order to achieve this, the researcher is based on the descriptive and analytical approach adopted for the analysis of the questionnaire and to test relations research and its variables. The research community (4) of hospitals in Sadr City, included've targeted 106 doctors and 222 nurses formed a whole (328) factor of the doctors and nurses of the hospitals surveyed, have been analyzing the data and test hypotheses using a number of appropriate statistical tools such as the arithmetic mean weighted and standard deviation to measure changes in the level of hospitals and the simple equation to test the impact of the decline. In the final analysis, the results showed the validity of the hypothesis main research, employing workplace spiritual increasing the sample's ability to make their attitudes towards work in a more positive, depending upon formulated a number of conclusions based on which a researcher in the development of a number of recommendations for hospitals surveyed, including: providing job security. And to prevent attacks on doctors and nurses through the activation of the protection of doctors and accounting aggressors law legally, and contrast enhancing behaviors ethical for doctors and nurses to deal with patients, and the need to create an encouraging regulatory environment to realize the meaning of the work of how each of the doctors and nurses, and this is done through the consolidation of vibrant relationship confidence among the workers themselves (doctors and nurses) and senior management.